Development and characterization of topical caffeine sunscreen formulation - Ab. Hadi, Hazrina; Rosli, Nur Amirah; Hamid, Zulfiki; Awadh, Ammar Ihsan JawaD (2015)
Caffeine prominent property as a natural sunscreen has received recent interests in researches on topical formulations incorporating this organic compound. The main objective of this paper is to evaluate caffeine behaviours in a broad-spectrum sprayable sunscreen preparation. Two types of sunscreen formulations were developed with and without presence of 2% caffeine. Parameters that may influence the formulation stability were assessed. This includes organoleptic tests (appearance, colour, thickness, feel), physical tests (rheology and centrifugal phase separation) and chemical test (pH measure). Findings in both formulations were similar for organoleptic test parameters. Immediately after preparation, both formulations appeared as whitish fluid with low viscosity of almost watery-like. Upon spraying a small amount on hand, the texture is found to be smooth and easily spreadable on skin. The conditions remain stable and findings were similar even after 7 days storage at room temperature. The pH values were all measured alkaline approximately at room temperature. The addition of 10% of sodium hydroxide into the formulation majorly contributed to the measured alkalinity. Thus, caffeine did not significantly change the pH of the formulation. Both formulations produced almost the same results whereby they behave like non-viscous Newtonian fluids. Our findings also indicate no phase separation of all triplicate samples with and without 2% caffeine. Through the comprehensive study done, it can be concluded that caffeine has the potential to be used in topical sunscreen formulations as caffeine helps in enhancing activities of UV filters without affecting formulation stability.